(untitled) (Research, Society and Development, 2020)
This article aims to investigate what researchers in the teaching field have produced about the approach of Universal Gravitation in Basic Education. For this, a systematic literature review was carried out looking for articles that dealt with the theme, with the aim of developing an analysis and reflection on the pedagogical strategies applied in Physics classes in High School, as well as exploring how the work developed in Higher Education can contribute to the development of the theme in Basic Education. Despite the small number of articles found on the theme, the works analyzed here suggest a diversity of alternatives for addressing the theme Gravitation, such as the use of texts, films, videos, images, virtual environments for learning, experimentation, History of Science, among others. However, despite a variety of proposals that recognize the study of Universal Gravitation as an essential knowledge for high school students, they are not always suited to the reality of public schools that often lack technological resources, or even, the need for continuing teacher training, so that these factors present themselves as a challenge to their implementation.